Long-Term Prognosis of Patients With Anti-N-Methyl-D-Aspartate Receptor Encephalitis Who Underwent Teratoma Removal: An Observational Study - Zhang, Hesheng; Xiong, Weixi; Liu, Xu; Liu, Wenyu; Zhou, Dong; Wu, Xintong (Frontiers in Neurology, 2022)
Objective This study aimed to evaluate the clinical characteristics and long-term surgical outcomes of patients with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis with teratoma. Methods Patients who were admitted to West China Hospital from June 2012 to June 2019 and diagnosed with anti-NMDAR encephalitis were enrolled in the study. Medical records were reviewed prospectively to gather clinical characteristic data. Patients were followed up at long-term every 3 months. Results This study included 192 patients, among whom 21 (10.9%) were detected with having a teratoma. Patients included 20 women, with a mean age of 24.62 ± 7.61 years. Seizure and psychiatric symptoms were the most dominant symptoms in both groups, followed by memory deficits. Central hypoventilation (52.4 vs. 17%, p < 0.001) and decreased consciousness (71.4 vs. 31.3%, p = 0.002) were significantly more frequent in patients with teratoma than in those without. Moreover, the anti-NMDAR antibody titer was higher (p = 0.021) and the baseline modified Rankin scale score was lower (p = 0.004) in patients with teratoma than in those without. First-line immunotherapy was performed in 21 (100%) patients with teratoma and 167 (97.7%) patients without teratoma. All patients with teratoma had the tumor removed. During follow-up, two (9.5%) patients with teratoma and 11 (6.4%) patients without teratoma died, whereas 1 (4.8%) patient with teratoma and 37 (21.6%) patients without teratoma had relapses. Overall, 19 (90.5%) patients with teratoma and 151 (88.3%) patients without teratoma achieved favorable clinical outcomes at the final follow-up. Conclusions With early detection and removal of teratoma, most patients with anti-NMDAR encephalitis and teratoma achieved a favorable long-term prognosis.